The Relationship between Disease, Work and Sickness Absence among Psoriasis Patients - Parvin MANSOURI; Fateme VALIRAD; Mirsaeed ATTARCHI; Saber MOHAMMADI; Shiva HATAMI; Seyed Farzin MIRCHERAGHI; Mohammadreza RAHBAR; Reza CHALANGARI (Tehran University of Medical Sciences, 2015)
Background: The aim of this study was to assess the prevalence of absenteeism in patients with psoriasis and determine the factors influencing the incidence of absenteeism in these patients. Methods: A cross-sectional study from December 2012 to November of 2013 was conducted on 192 psoriasis patients referred to the Dermatology Clinic of Imam Khomeini Hospital, Tehran, Iran. The number day of absence from work due to psoriasis in the last year was asked from the patients; the absence of 7 days has been considered as short-term and more than 7 days as long-term. Logistic regression was used to data analysis. Results: Sickness absence in 21.4% of patients was positive. The average numbers of days of absence were 10.25 and the duration of absence from work in 48.7% were long-term ≥7 days. 51.3% had short-term absence (<7 days). Among disease factors: moderate to severe disease (SAPASI score >10), palms and soles involvement, joint problems and radiation therapy and among job factors: hazardous physical and chemical exposures in the workplace, non-office work, disability, exacerbations of disease on work days and problem on employment were associated with high incidence of sickness absence. Conclusion: Psoriasis with its chronic and recurrent nature especially in higher severities causes disabilities that deeply affect Work performance and can decrease the efficiency. In better management of psoriasis patients, physicians should pay special attention to occupational factors.   Keywords: Sickness absence, Occupational stress, Psoriasis patients, SAPASI